Study on the Structural Optimization of Diffuser Guide Vanes for LNG High-Pressure Pump Expander - YANG Linchun (Cailiao Baohu)
The guide vanes of the high-pressure pump at the Jingtang LNG receiving station frequently fail， potentially generating metal fragments that threaten the safety of downstream systems.In order to extend the service life of the guide vanes， ANSYS software was used to establish a model and conduct strength simulation calculations and fatigue simulation analysis on the diffuser guide vanes of the high-pressure pump.Results showed that cracks or fractures were more likely to occur near the hub of the impeller blades， with an increased risk of fatigue fracture at the root of the inlet edge.By changing the material from cast aluminum to forged aluminum 6061-T6， the mechanical properties were significantly improved.Additionally， it was found that when the thickness of the guide vane was increased from 3.5 mm to 5.0 mm， the membrane plus bending stress at the root was reduced by 40%to 50%.Enlarging the root fillet of the guide vane effectively reduced stress concentration，thereby decreasing the risk of crack initiation and significantly enhancing the fatigue resistance of the blade.Based on engineering application data， these improvements effectively resolved the operational issues encountered in the LNG high-pressure pump， enhancing its reliability and safety， and ensuring the stable operation of the LNG transmission system.